6=2X-4

Simple and best practice solution for 6=2X-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=2X-4 equation:


Simplifying
6 = 2X + -4

Reorder the terms:
6 = -4 + 2X

Solving
6 = -4 + 2X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-2X' to each side of the equation.
6 + -2X = -4 + 2X + -2X

Combine like terms: 2X + -2X = 0
6 + -2X = -4 + 0
6 + -2X = -4

Add '-6' to each side of the equation.
6 + -6 + -2X = -4 + -6

Combine like terms: 6 + -6 = 0
0 + -2X = -4 + -6
-2X = -4 + -6

Combine like terms: -4 + -6 = -10
-2X = -10

Divide each side by '-2'.
X = 5

Simplifying
X = 5

See similar equations:

| 3ab+4ac= | | 6x^2+11x-17=-7 | | 2=.13x | | x+32=55 | | c=18+.5C | | x^2+22x=0 | | 1-c=-13+-8c | | 2(1-x)=3(1+2x)+5 | | 2(4+x)=8+3x | | 5t-13=12-5t | | 3x-6=18+7x | | x+8=-5 | | x-3=2x+6 | | 2(X+3)=4(X-2) | | 3(X+2)=X | | 8T+13-T=4T+14 | | 8x+10=66 | | X+10=2X | | 8X-6=6X | | 2(x+5)-3(5-x)=10 | | 5x-4=5+2x | | 6x+8=2x-12 | | 8(x-1)=8-4(2x-3) | | (3x+2)(7x+4)=8 | | 2x+9=1-3x | | 8-3x=10-x | | 3(x-2)=2x-4 | | 9x+12y=18 | | 3x+4-6x=46 | | 18b^2-222b+540=0 | | -12m^2+52m-56=0 | | 3x+4x=14 |

Equations solver categories